Balancing learning standards with students' diverse learning needs - Angell, Maureen; Films for the Humanities & Sciences (Princeton, N.J. : Films for the Humanities & Sciences, 2006)
If diversity and special needs are prominent factors in a learning environment, teachers may have to juggle mandated standards with students' personal challenges. This video addresses that balancing act, demonstrating how experienced educators have mastered it. Focusing on multilevel instructional planning, the program explores the use of educational channels, individualized support, and interpersonal engagement--showing how to deliver lessons and assess student progress based on communication style, learning preference, and other variables. An extensive bonus interview with Dr. Diane Ashby, Dean of Illinois State University's College of Education, is included
Title from title screen
Presenter, Maureen Angell
DVD format
Keywords: Lesson planning; Education -- Standards; Students with disabilities